The Role of Artificial Intelligence in Arabic Language Processing: Ethical Challenges and Development Prospects - Saiah, Nadia Lekdjaa Djelloul; Wafaà, Diab Narimene (Al-Wazan: Journal of Arabic Education, 2025)
This study investigates the role of artificial intelligence (AI) in Arabic language processing, focusing on both its developmental potential and the challenges that threaten the language’s integrity and identity. Despite progress in natural language processing (NLP), the Arabic language still faces substantial barriers due to its intricate grammatical rules and semantic depth, which make it more complex to integrate into AI systems compared to other languages. In addition to technical obstacles, the application of AI raises ethical concerns—particularly around preserving the authenticity of Arabic and protecting intellectual property. Issues such as uncredited AI-generated content and reduced human involvement in language formulation may compromise the credibility and originality of information. The study aims to offer future-oriented solutions that address these ethical challenges while promoting a balanced approach between leveraging AI technologies and safeguarding the linguistic heritage of Arabic. Adopting a qualitative, literature-based methodology with a focus on ethical, linguistic, and technological analysis, the research underscores the urgent need for ethical and regulatory frameworks to guide AI implementation in this domain. The findings highlight the importance of continuous investment in research and development to support Arabic’s sustainable integration into AI-driven platforms. As a contribution, the study provides a conceptual foundation for responsible innovation, advocating for policies that protect the identity of the Arabic language while enabling its evolution within the digital age